2017
DOI: 10.1371/journal.pone.0184930
|View full text |Cite
|
Sign up to set email alerts
|

Significance of chronic toxoplasmosis in epidemiology of road traffic accidents in Russian Federation

Abstract: Studies carried out in Moscow residents have revealed that the prevalence of chronic toxoplasmosis is very close to those in countries of Eastern and Central Europe. Our findings also demonstrated a statistically significant relationship between the rate of traffic accidents and the seroprevalence of chronic toxoplasmosis in drivers who were held responsible for accidents. The latter was 2.37 times higher in drivers who were involved in road accidents compared with control groups. These results suggest that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…In total, 11 studies comparing seropositivity to T. gondii with the risk of being involved in a TA were identified (Flegr et al ., 2002; Yereli et al ., 2006; Flegr et al ., 2009; Kocazeybek et al ., 2009; Galvan-Ramirez et al ., 2013; Samojlowicz et al ., 2013; Alvarado-Esquivel et al ., 2015; Shotar et al ., 2016; Sugden et al ., 2016; Stepanova et al ., 2017; Burgdorf et al ., 2019), showing an overall OR of 1.69 (95% CI 1.20–2.38, p = 0.003), see Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 11 studies comparing seropositivity to T. gondii with the risk of being involved in a TA were identified (Flegr et al ., 2002; Yereli et al ., 2006; Flegr et al ., 2009; Kocazeybek et al ., 2009; Galvan-Ramirez et al ., 2013; Samojlowicz et al ., 2013; Alvarado-Esquivel et al ., 2015; Shotar et al ., 2016; Sugden et al ., 2016; Stepanova et al ., 2017; Burgdorf et al ., 2019), showing an overall OR of 1.69 (95% CI 1.20–2.38, p = 0.003), see Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Stepanova et al showed that due to the effect of toxoplasmosis, which caused a slower reaction time and reduced concentration in drivers, there was a statistically signi cant relationship between the rate of tra c accidents and the prevalence of toxoplasmosis. Hence, the prevalence of toxoplasmosis was 2.37 times higher in drivers who participated in road accidents than in control groups (21).…”
Section: Discussionmentioning
confidence: 81%
“…Bei weltweit mehr als zwei Milliarden infizierten Menschen und einer hohen Variabilität der Infektionsraten (von 8,6% in Norwegen bis 60,4% in Brasilien; ▶Tab. 1) können jedoch auch kleine Effekte eine große Wirkung haben: Eine Häufung von Verkehrsunfällen (13,30) und Suizidversuchen sowie Suiziden (2, 6) nach abgelaufener Toxoplasmose-Infektion ist tatsächlich zu verzeichnen und lässt auf vermehrte Aggressivität, Impulsivität und risikoreicheres Verhalten schließen. Da die Durchseuchung der Bevölkerung in Deutschland etwa 50% beträgt, geht das uns alle durchaus an: Eine abgelaufene Infektion mit Toxoplasma gondii ist nicht völlig ohne Folgen.…”
Section: Spitzer Ulmunclassified